Sustainable Circular Bioeconomy - Nallapaneni, Manoj Kumar; Haque, Md Ariful; Patwary, Sarif (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint delves deep into the principles, practices, and possibilities of the sustainable circular bioeconomy. Within these pages, you will find a wealth of knowledge and insights contributed by experts, researchers, and practitioners who have dedicated their lives to advancing the boundaries of sustainability. Each chapter of this reprint is carefully crafted to provide a holistic view of the subject, covering a wide range of topics, including renewable energy, waste management, food-energy-water nexus, digital innovation in sustainability, aquaculture, agriculture, biotechnology, and more.